دراسة الكفاءة الاقتصادية لزراعة الموز في البيوت البلاستيكية في محافظة طرطوس - يعقوب غسان; قنوع نزار (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يتضمن البحث دراسة واقع زراعة وإنتاج الموز في البيوت البلاستيكية في محافظة طرطوس إذ بلغ عدد البيوت البلاستيكية المزروعة بالموز عام 2002م حوالي 1045 بيتاً وهذا يشكل ما نسبته 1,35% من إجمالي عدد البيوت البلاستيكية في القطر العربي السوري المزروعة بالخضار المختلفة والمقدرة عام 2003 بحوالي 70476بيتا, ثم تأتي محافظة اللاذقية في المرتبة الثانية بزراعة الموز إذ يزرع فيها 73 بيتاً بلاستيكياً عام 2002. وجدنا أن عدد البيوت البلاستيكية المزروعة بالموز في منطقة بانياس عام 2002 حوالي 637 بيتاً أي ما نسبته 57% من إجمالي عدد البيوت المزروعة بالموز في الساحل السوري. في دراسة تحليلية اقتصادية لمشروع زراعة الموز في خمس صالات مساحتها حوالي 5000 م2 وجدنا أن إجمالي التكاليف مع ريع الأرض بلغ 209121 ليرة سورية. وأن كلفة إنتاج كيلو غرام واحد من الموز وصل إلى حوالي 26.14 ليرة سورية وعند قياس بعض المؤشرات الاقتصادية بدون الموسم التحميلي وجدنا أن تكلفة إنتاج 100 ليرة سورية تساوي 75 ليرة سورية وأن زمن استعادة رأس المال يساوي 1.86 سنة. ومعامل الربحية يساوي 53.8 % ومع الموسم التحميلي أصبح زمن استعادة رأس المال يساوي 1,45 سنة ومعامل الربحية 69%. This research includes the study of banana cultivation and production in plastic houses in Tartous province, where /1045/ plastic houses were planted with banana in 2002 (about 1.35% of the total number of plastic houses cultivated with various vegetables), whereas /73/ plastic houses were cultivated with banana in Lattakia province in the same year. We found that the number of plastic houses cultivated with Banana in Banyas region (Tartous province) was /637/ and formed about 57% of the total number of plastic houses cultivated with banana in the Syrian coastal region in 2002. We found in an economical analytical study of banana production project in five plastic houses (area 5000 m2) planted with banana that the total expenses, including the land rent, has exceeded /209121/ Syrian Pounds, and the cost of producing one kilogram of banana was about /26.14 S.P. When some economic indicators were measured (excluding double cropping) we found that the cost of producing /100/ S.P. equals /75/ S.P., and the time for resuming the capital money is /1.56/ years, and the profitability rate is 53.8 %. In the case of double cropping, the time for resuming the capital money is /1.45/ years, and the profitability rate is 69%.